Beyond inhaled medications: precision medicine and biologic therapies targeting the IL-33/TSLP/type 2 axis in COPD - Song, Guo-qiang; Chen, Bangsheng; He, Tian-li; Hu, Guo-qiang (Frontiers in Immunology, 2026)
Chronic obstructive pulmonary disease (COPD) is characterized by persistent airflow limitation and chronic airway inflammation, traditionally managed with inhaled bronchodilators and corticosteroids. However, a significant subset of patients exhibits suboptimal response to these inhaled therapies, and disease progression remains challenging to control effectively. Recent advances in understanding the inflammatory pathways underlying COPD have led to the development of biologic agents targeting critical cytokines and their receptors, including IL-4 receptor (IL-4R), IL-5, IL-5 receptor (IL-5R), IL-33, ST2, and thymic stromal lymphopoietin (TSLP). Emerging drugs such as JKN2401, TQC2731, and tezepelumab demonstrate promising therapeutic potential by modulating these specific inflammatory mediators. This review comprehensively summarizes the pathophysiological roles of these cytokines in COPD, the current progress in biologic drug development targeting these molecules, and the outcomes of recent clinical trials. By elucidating these novel therapeutic avenues, the article aims to provide a theoretical foundation and clinical guidance for precision medicine approaches in COPD management beyond conventional inhaled treatments.